Effect of soybean processing on starter pig performance and nutrient digestibility - D F Li; R C Thaler; Jim L Nelssen; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1989)
One hundred sixty-eight pigs were used to evaluate the effect of soybean processing on starter pig performance and nutrient digestibility. Soybean products tested were commercial soybean meal, full-fat roasted soybeans from either a Roast-A-Tron or Rickles Roaster, extruded soybeans, and steam-flaked soybeans. Pigs fed soybeans from the Rickles Roaster had lower average daily gain, average daily feed intake, and feed efficiency than pigs fed the other soybean products. Rickles soybeans had lower apparent digestibility of nitrogen, dry matter, total fat, and long chain fatty acids than the other treatments. Pigs fed steam-flaked soybeans had the second lowest growth rate. These results indicate that soybeans processed through a Rickles Roaster are not suitable for starter pigs. Based on the results of this experiment, we conclude that processing method may be a major factor influencing soybean utilization by the early weaned pig.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Soybeans; Pig; Performance; Digestibility; Roasting; Steam flaking; Extruding